P127 An audit of the management of complainants of sexual assault compared with the British association for sexual health and HIV (BASHH) 2011 guidelines. (23rd May 2012) - McGranahan, M; Gupta, N; Goold, P
Abstract : Background: The revised BASHH guidelines for the management of sexual assault were published in 2011. Introduction of a new electronic patient record (EPR) at a sexual health clinic provided an opportunity to audit the management of sexual assault. Aims: To review the clinical care of complainants of sexual assault against the auditable outcome measures identified in the guidelines. Methods: The EPR of patients attending between 1 August 2010 and 31 July 2011 was searched using the term "assault." Cases reporting a sexual assault for the first time were included and reviewed against the auditable outcome measures. Demographic data and sexually transmitted infection (STI) test results were recorded. Results: 236 records were identified but 99 cases fulfilled the inclusion criteria. Of the 14 auditable outcomes, only HIV risk assessment reached the 100% standard and seven achieved above 60% concordance (offer and provision of HIV post-exposure prophylaxis, emergency contraception, follow-up tests, forensic medical examination, hepatitis B vaccine and detailed history of assault). Child protection assessment was documented in 57% of under-19s. 28% had the recommended STI tests and 16% were offered STI prophylaxis. There were no self-harm risk assessments documented. STI prevalence was: Gonorrhoea 8%, Chlamydia 9%, HIV 2%, Hepatitis C Virus and Trichomonas 1%. Conclusion: Low STI testing rates overall are explained by Hepatitis B and C testing not previously being a requirement unless there was a specific risk identified. The clinic conducts an automatic risk assessment for under-16s but not for under 19s. STI prevalence was high. A sexual assault pro-forma will be recommended and improved documentation is required.